Food policy - Gittinger, J.P., ed. (John Hopkins BaltimoreUS, 1987)
Contains collection of papers which is divided into 5 sections each on a particular aspect of food supply. Gives overview of the current thinking about food policy and discusses the world food situation. Examines food production focusing on problems of low income producers, women, and discusses ways of improving the nutritional quality of food. Discusses food security, trade, aid, distribution issues and price policy. Examines nutrition problems and the development of policies to address them. Reviews the experience in food and nutrition planning and recommends that it be broadly integrated.